Social Inclusion through ICT: Identifying and Overcoming Barriers to ICT Use1. (20th January 2016) - Taylor, Dan; Packham, Gary
Abstract : Creative approaches to ICT training and development can help to overcome barriers to ICT adoption and usage, leading to increased social inclusion.